Astrocytic hamartoma in a patient heterozygous for RIM1 mutation associated-retinal dystrophy. (4th May 2022) - Chiou, Yi-Ran; Cheng, Hui-Chen; Wang, An-Guor
ABSTRACT: Background: Autosomal-dominant cone-rod dystrophy 7 (CORD7) has been documented in association with RIM1 mutation (c.2459 G>A). We report a patient with retinal dystrophy who was heterozygous for RIM1 missense variant with a newly found point mutation (c.4036 G>T). Clinical findings of this genetic variant manifested differently from a typical CORD7. In addition, astrocytic hamartomas at bilateral optic discs are also a unique feature, which has not been described in CORD previously. Materials and methods: Medical records of this patient were retrospectively reviewed. Genetic testing with whole exon sequencing was performed. Results: This 43-year-old female with history of decreased night vision since childhood came to our hospital complaining of blurred vision in both eyes for more than half a year. Her best-corrected visual acuity was 20/200 in both eyes. Dilated fundoscopic examination revealed symmetric diffuse atrophy of retinal pigment epithelium with peripheral pigmentary clumps. Also, optic disc astrocytic hamartomas were found bilaterally. Optical coherence tomography revealed extensive disruption of inner segment/outer segment junction in both eyes. Visual field test showed severe peripheral defect sparing central vision. Electroretinogram demonstrated both rod and cone cells abnormalities. Subsequent genetic testing reported heterozygosity for the RIM1 (c.4036 G>T) mutation. Conclusions: This is the first reported case of RIM1 mutation-associated retinal dystrophy with a newly found point mutation (c.4036 G>T), which presented differently from a typical CORD7 and more similarly to the phenotype of RP. Furthermore, our finding of bilateral optic disc astrocytic hamartomas has not been reported in association with CORD previously.